Thermal Performance Analysis for Optimal Passive Cooling Heat Sink Design - Nur Warissyahidah Badrul Hisham; Fatimah Sham Ismail; Muhammad Azmi Ahmed Nawawi (Universitas Ahmad Dahlan, 2017)
Recent advances in semiconductor technology show the improvement of fabrication on electronics appliances in terms of performance, power density and even the size. This great achievement however led to some major problems on thermal and heat distribution of the electronic devices. This thermal problem could reduce the efficiency and reliability of the electronic devices. In order to minimize this thermal problem, an optimal cooling techniques need to be applied during the operation. There are various cooling techniques have been used and one of them is passive pin fin heat sink approach. This paper focuses on inline pin fin heat sink, which use copper material with different shapes of pin fin and a constant 5.5W heat sources. The simulation model has been formulated using COMSOL Multiphysics software to stimulate the pin fin design, study the thermal distribution and the maximum heat profile.